Ligand field variations: tuning the toroidal moment of Dy6 rings. Issue 14 (13th March 2015) - Baniodeh, Amer; Magnani, Nicola; Bräse, Stefan; Anson, Christopher E.; Powell, Annie K.
Abstract : We show how the toroidal moment in Dy6 cyclic coordination clusters can be tuned and optimised. Abstract : Two new examples of Dy6 cyclic coordination clusters have been synthesised in order to discover how the toroidal moment in such a motif can be tuned and optimised.